A pilot cluster randomised controlled trial of a support and training intervention to improve the mental health of secondary school teachers and students – the WISE (Wellbeing in Secondary Education) study. (December 2016) - Kidger, Judi; Stone, Tracey; Tilling, Kate; Brockman, Rowan; Campbell, Rona; Ford, Tamsin; Hollingworth, William; King, Michael; Araya, Ricardo; Gunnell, David
Abstract Background Secondary school teachers are at heightened risk of psychological distress, which can lead to poor work performance, poor quality teacher-student relationships and mental illness. A pilot cluster randomised controlled trial (RCT) – the WISE study – evaluated the feasibility of a full-scale RCT of an intervention to support school staff's own mental health, and train them in supporting student mental health. Methods Six schools were randomised to an intervention or control group. In the intervention schools i) 8–9 staff received Mental Health First Aid (MHFA) training and became staff peer supporters, and ii) youth MHFA training was offered to the wider staff body. Control schools continued with usual practice. We used thematic qualitative data analysis and regression modelling to ascertain the feasibility, acceptability and potential usefulness of the intervention. Results Thirteen training observations, 14 staff focus groups and 6 staff interviews were completed, and 438 staff (43.5 %) and 1, 862 (56.3 %) students (years 8 and 9) completed questionnaires at baseline and one year later. MHFA training was considered relevant for schools, and trainees gained in knowledge, confidence in helping others, and awareness regarding their own mental health. Suggestions for reducing the length of the training and focusing on helping strategies were made. A peer support service was established in all intervention schools and was perceived to be helpful in supporting individuals in difficulty – for example through listening, and signposting to other services - and raising the profile of mental health at a whole school level. Barriers to use included lack of knowledge about the service, concerns about confidentiality and a preference for accessing support from pre-existing networks. Conclusions The WISE intervention is feasible and acceptable to schools. Results support the development of a full-scale cluster RCT, if steps are taken to improve response rates and implement the suggested improvements to the intervention. Trial registration International Standard Randomised Controlled Trial Number:ISRCTN13255300 retrospectively registered 28/09/16.